(3GdJLGQI GdGdcJQhfjIs - (3NjQj eUWai(B, (3cJGfgs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2009)
(3GdeYdheGJjI h GJNGP GdbQGQ , eaghe GdJLGQI GdGdcJQhfjI , efXeI GdJLGQI GdYGdejI (B(wto) (3GdGfJQfjJ h HYV JWHjbGJ GdJLGQI GdGdcJQhfjI , OhQ GdHfhc GdGdcJQhfjI aj OYe GdJLGQI GdGdcJQhfjI , edGeM GdJLGQI GdGdcJQhfjI aj GdGbJUGO GdGQOfj , GdJLGQI GdGdcJQhfjI aj SjGb GdYhdeI h GdNUNUI , eaghe GdMcheI GdGdcJQhfjI h GdJYdje GdGdcJQhfj , GdGSJQGJjLjI GdGdcJQhfjI GdQbejI GdTGedI , GdGReGJ GdeGdjI h GdGbJUGOjI GdYGdejIs
(3eQGLY U(B.391s
Keywords: (3GdEbJUGO(B- (3GdCQOfs; (3GdJLGQIs; (3GdJLGQI(B- (3GdCQOfs; (3efXeI GdJLGQI GdOhdjIs